Development of Technology Profiles for the Transfer of Energy- and Resource Saving Technologies - Lysenko, V.S.; Yehorov, S.O.; Pokshevnitskaya, T.V. (Science and Innovation, 2024)
The article deals with methodological framework for the development of technology profiles for the System of Energy- and Resource Saving Technology Transfer. The compliance with the methodology and standards of the European Innovation Relay Centers (the IRC network; since 2008, the EEN), the Russian Technology Transfer Network (RTTN), and Ukrainian Technology Transfer Network UTTN has been established to be the main principle of the development of technology requests and offers.